Chapter 15: Careers in turbulent environments: the impact of ‘Brexit’ on career motivations and behaviour in the United Kingdom - Dickmann, Michael; Parry, Emma; Chudzikowski, Katharina (Edward Elgar Publishing, 2023)
This chapter explores the effects that the ‘hostile environment’ policy of the British government and the eventual exit of the United Kingdom (UK) from the EU, has had on the careers of international workers. Using insights from the career and hostile environment literatures, it concentrates on institutional, psychological and interactional perceptions that impact individuals’ career motivations and behaviors. Specifically, we explore and illustrate this using two cases of EU citizen who have lived and worked in the UK. We trace the development of their thinking and acting in the evolving career space over time to understand the effects of ‘hostile environments’ on their well-being, their identification with the host environment, their identity, career plans and coping approaches.
Keywords: boundaries/boundary crossing; career shock; crisis and disruption; job mobility; migration; political systems and relocation